Broken Pots, Mended Dreams: Concepts, Causes, and Effects of Teenage Pregnancy in Outreach Barangay - Solar, Nick John (Social Sciences and Development Review, 2019)
This study aimed to determine the concepts, causes and effects of teenage pregnancy among selected residents in outreach barangay as an entire group and when classified as to sex. Mixed descriptive and phenomenological methods of research were used, utilizing 50 selected residents as respondents, 7 or 14% were male and 43 or 86% were female, whom were selected through random sampling. The data were obtained through the use of a survey questionnaire. Based on the findings, results revealed that when respondents were categorized by the entire group, teenage pregnancy was the transition period between childhood and adulthood, while, incident of teenage pregnancy was high and was avoided in the outreach barangay were the least concepts of teenage pregnancy exist. The top cause of teenage pregnancy was lack of sex education while, the least cause of teenage pregnancy was the socio-economic status. The effect of teenage pregnancy was primarily an incomplete education and the least effect will be isolation and rejection of friends or community. Furthermore, no significant differences and relationship on the concepts, causes and effects of teenage pregnancy resulted among selected residents in outreach barangay. Lived Experiences among Respondents of Teenage Pregnancy were divided into subthemes: (a) socio-economic status (b) health and (c) family relationship. Coping to Survive the Dilemmas of Teenage Pregnancy were divided into subthemes: (a) family support and (b) prayers and believing to the help Most Powerful Almighty. Statistical treatments were mean, standard deviation and t-test for independent samples set at 0.05 alpha level. All computations were done via SPSS software.